Charter school funding considerations - Kiracofe, Christine; Hirth, Marilyn A.; Hutton, Tom (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Much has been written about how public schools in the United States are funded. However, missing in the current literature landscape is a nuanced discussion of funding as it relates to public charter schools. This text, authored by researchers and professionals working in the charter school world, provides readers with a comprehensive overview of issues related to the funding and operation of charter schools. The book opens with an introduction to charter schools and how they are funded. The financial management and oversight of charter schools and issues related to funding equity, including how charter schools impact district school finances, are addressed. Special considerations for charter schools related to serving special education students and transportation issues are also addressed. After reading this book, readers will have a thorough understanding of how charter schools are funded and managed financially"-- Provided by publisher.
Keywords: Charter schools -- United States -- Finance.; Education -- Schools -- Types -- Charter.; Independent schools, private education.; elektronické knihy; electronic books